Molecular Biology of Cancer : Mechanisms, Targets, and Therapeutics - Pecorino, Lauren (Oxford, United Kingdom Oxford University Press, 2016)
"The most engaging and accessible account of cancer biology that makes the link between our understanding of cancer and the development of new therapeutics crystal clear. -- Molecular Biology of Cancer: Mechanisms, Targets, and Therapeutics offers an engaging and manageable route into the complex subject of cancer biology. Using the hallmarks of cancer as a foundation, the book describes the cellular and molecular mechanisms underpinning the transformation of healthy cells into cancer cells. -- after discussing a specific biological hallmark of cancer, each chapter shows how this knowledge can be directly applied to the development of new targeted therapies, giving you a clear appreciation of how the theory translated to tackling the disease. The new edition gives a contemporary account of the field, drawing on the latest research but presenting it in a manner that you will find easy to understand. -- New to this edition: *New full colour diagrams help you visualize key concepts more effectively *Separate chapters for growing areas of cancer biology: Metastasis, Angiogenesis, Infectious Agents and Inflammation, and Technology and Drug and Diagnostics Development *Coverage of range of new topics, including immune checkpoints, studying gene function by CRISPR-Ca9, newly proposed mechanisms for the role of obesity in cancer, non-coding RNAs, and the role of exosomes in intercellular communication *Latest details of newly approved therapeutics"
Include Color Illustration, Glossary and Index
Keywords: Cancer--Molecular aspects -- Cancer cells -- Cancer cells--Growth